Efficient Copper-Catalyzed Synthesis of Substituted Pyrazoles at Room Temperature - Wang, Haifeng; Sun, Xiangli; Zhang, Shuangling; Liu, Guanglu; Wang, Chunjie; Zhu, Lili; Zhang, Hui (Synlett, 2018)
An efficient method for the synthesis of pyrazoles through a copper-catalyzed condensation reaction has been developed. The new catalytic system not only maintained a broad substrate scope but was also active under acid-free reaction conditions, overcoming the conventional requirement for an acid-catalyzed system. Furthermore, the copper catalyst enabled this reaction to be performed at room temperature and in a short reaction time.
Keywords: pyrazoles; condensation reaction; copper catalysis; arylhydrazines; sulfonyl hydrazides